Influence of intrauterine and extrauterine growth on neurodevelopmental outcome of monozygotic twins - R.K. Reolon; N.T. Rotta; M. Agranonik; A.A. Moura da Silva; M.Z. Goldani (Brazilian Journal of Medical and Biological Research, 2008)
There have been indications that intrauterine and early extrauterine growth can influence childhood mental and motor function. The objective of the present study was to evaluate the influence of intrauterine growth restriction and early extrauterine head growth on the neurodevelopmental outcome of monozygotic twins. Thirty-six monozygous twin pairs were evaluated at the corrected age of 12 to 42 months. Intrauterine growth restriction was quantified using the fetal growth ratio. The effects of birth weight ratio, head circumference at birth and current head circumference on mental and motor outcomes were estimated using mixed-effect linear regression models. Separate estimates of the between (interpair) and within (intrapair) effects of each measure on development were thus obtained. Neurodevelopment was assessed with the Bayley Scales of Infant Development, 2nd edition, by a psychologist blind to the exposure. A standardized neurological examination was performed by a neuropediatrician who was unaware of the exposures under investigation. After adjustment, birth weight ratio and head circumference at birth were not associated with motor or mental outcomes. Current head circumference was associated with mental but not with motor outcomes. Only the intrapair twin effect was significant. An increase of 1 cm in current head circumference of one twin compared with the other was associated with 3.2 points higher in Mental Developmental Index (95%CI = 1.06-5.32; P < 0.03). Thus, no effect of intrauterine growth was found on cognition and only postnatal head growth was associated with cognition. This effect was not shared by the co-twin.